Tradition and modernity: an obsolete dichotomy? Binary thinking, indigenous peoples and normalisation. Issue 9 (1st September 2016) - Germond-Duret, Celine
Abstract: The debates over Indigenous peoples and development are often framed within the discussion on the shift towards modernity, the imposition of economic liberalism and resistance against external interventions, with a tendency to see Indigenous peoples as a possible alternative to the world economic order. However, looking at many development agencies' discourses, the idea that Indigenous peoples will actually benefit from modernity prevails. The literature is divided along these two conflicting views and dominated by binary oppositions: traditional/modern; backward/advanced; sustainable/unsustainable, etc. This article discusses the tradition/modernity dichotomy and raises the following questions: is it relevant to think in terms of modernity/tradition in the case of Indigenous peoples? What does the use of such a dichotomy imply? What is the alternative? The article demonstrates that this binary opposition is neither relevant nor desirable, and that a new analytical framework is required. Instead, it proposes using a normalisation framework, which focuses on the attempts made to 'normalise' Indigenous peoples and to encourage them to comply with existing social and economic models.